The Vicissitudes of Homophobic Victimization in Adolescence: An Explorative Study - Pace, Ugo; D’Urso, Giulio; Fontanesi, Lilybeth (Frontiers in Psychology, 2020)
This study investigates the role of parental and peer relationships’ quality on homophobic victimization and possible consequences on mental health during adolescence. Participants were 394 adolescents, (41.6% male and 58.4 % female) aged 15-20 years (M = 16.55; SD = .85), attending the third and fourth classes of public high schools in Italy. Participants completed the Homophobic Bullying Scale to evaluate homophobic victimization toward gays and lesbians or assumed homosexuals, the Symptom Check-list-90 to evaluate mental health, and the Inventory of Parent and Peer Attachment to investigate quality of peer and parental relationships (in term of communication, disaffection and trust). Results show how quality of peer relationships is not connected with victimization, as well as quality of parental relationships is linked with homophobic victimization, that is also connected with anxiety and somatization problems. Theoretical and educational implications were discussed.